Evaluation of clinicians' knowledge, attitudes, and planned behaviors related to an intervention to improve acute respiratory infection management. (June 2020) - Hruza, Hayli R.; Velasquez, Tania; Madaras-Kelly, Karl J.; Fleming-Dutra, Katherine E.; Samore, Matthew H.; Butler, Jorie M.
Abstract: Background: Acute respiratory tract infections (ARIs) are commonly diagnosed and major drivers of antibiotic prescribing. Clinician-focused interventions can reduce unnecessary antibiotic prescribing for ARIs. We elicited clinician feedback to design sustainable interventions to improve ARI management by understanding the mental framework of clinicians surrounding antibiotic prescribing within Veterans' Health Administration clinics. Methods: We conducted one-on-one interviews with clinicians ( n = 20) from clinics targeted for intervention at 5 facilities. The theory of planned behavior guided interview questions. Interviews were audio recorded and transcribed for qualitative analysis. An iterative coding approach identified 6 themes. Results: Emergent themes: (1) barriers to appropriate prescribing are multifactorial and include challenges of behavior change; (2) antibiotic prescribing decisions are perceived as autonomous yet, diagnostic uncertainty and perceptions of patient demand can make prescribing decisions difficult; (3) clinicians perceive variation in peer prescribing practices and influences; (4) clinician-focused interventions are valuable if delivered with sensitivity; (5) communication strategies for educating patients are preferred to a shared decisions process; and (6) team standardization of practice and communication are key to facilitate appropriate prescribing. Clinicians perceived audit-and-feedback with peer comparison, academic detailing, and enhanced patient communication strategies as viable approaches to improving appropriate prescribing. Conclusion: Implementation strategies that enable clinicians to overcome diagnostic uncertainty, perceived patient demand, and improve patient education are desired. Implementation strategies were welcomed, and some were more readily accepted (eg, audit feedback) than others (eg, shared decision making). Implementation strategies should address clinicians' perceptions of antibiotic prescribing practices and should enhance their patient communication skills.